A opinião dos alunos sobre o Ensino Médio Integrado em Administração do Instituto Federal de São Paulo/Câmpus Suzano - Ferreira, Maria Aparecida Bueno (2019)
This work has the objective of researching technical high school, which is believed to enable integral education, comprehending physical, social, cultural scientific and technological aspects. The concept of integral education was applied by Rousseau, who supported the full development of students, aiming at autonomous education for social interaction. This education modality has always been interesting to me for the relevance of education as a basic and universal right, of crucial importance for the construction of an autonomous nation. The theoretical basis is formed, in principle, in the bibliographic production by Rosa Fátima de Souza, Clarice Nunes, Bianca B. Zucchi, Luciana Neves Loponte, Maria Ciavatta and Dante Henrique Moura, among others. The research aims at analyzing the perceptions of second year students of the technical high school course in Business provided by Instituto Federal de Educação, Ciência e Tecnologia de São Paulo, IFSP/Câmpus Suzano, following the principles of qualitative research as theoreticalmethodological basis and using the bibliographic research, the documental research and questionnaires as techniques of data collection. After the application of the questionnaires, they were transcribed and analyzed by the means of content analysis. The results led to two main aspects. The first was that students consider there is integration in the course, but also remarked the existence of hindrances, such as material and infrastructural problems and also excess of excess of school hours. The second one refers to the results found in the bibliographic analysis of technical high school and shows that there is a distance between the principles contained in the policy proposed and its actual implementation, especially in relation to the curriculum integration between the common nucleus (high school subjects) and the technical, specific subjetcs. The conclusion was that the majority of students had a positive view of the course and the structure offered by the campus and that they were willing to continue the course, despite the long school hours. With reference to the role of the institution, it must focus the polytechnic education by means of a collective and participative form in the formulation of its politicalpedagogical projects and course plans